Dancing with ‘The Other’: Challenges and Opportunities of Deepening Democracy through Participatory Spaces for Refugees - Rast, Maria Charlotte (Social Inclusion, 2018)
Due to the so-called refugee crisis and the Netherlands’ development into a ‘participation society’, refugee reception there has recently shifted its focus to early and fast participation. In this context, numerous community initiatives have emerged to support refugee reception and integration. Compared to earlier restrictive approaches, refugee reception through active engagement of newcomers in community initiatives seems to promise a more inclusive approach, a deepening of democracy. However, such initiatives have internal and external challenges that might inhibit refugees’ active participation and the initiatives’ adoption of inclusive approaches. In this qualitative research, we have explored the challenges and opportunities for active participation and inclusion of refugees in community initiatives, considering the context of normalizing exclusive discourses and increasingly neoliberal policies on refugee reception.